Incidence of Puerperal Pyrexia in Women with Meconium-Stained Amniotic Fluid - Sadaf Zulfiqar, Anam Zulfiqar, Rabia Akram, Yasmeen Gul, Asia Raza, Bushra Sultana, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Puerperal pyrexia is a common postpartum complication that can lead to severe health risks for mothers. One of the contributing factors is meconium-stained amniotic fluid (MSAF), which is associated with various complications, including puerperal pyrexia. Despite its clinical importance, the relationship between MSAF and puerperal pyrexia remains under-researched. Objectives: This study aimed to investigate the incidence of puerperal pyrexia in women with MSAF, examine the impact of the severity of meconium staining, and identify associated risk factors in a cohort of postpartum women. Study Design & Setting: A retrospective observational study was conducted at Obstetrics and Gynaecology Dr Akbar Niazi Teaching Hospital Islamabad from January 2023 to June 2023. The study included 120 women who delivered at the facility and had MSAF. Demographic, clinical, and obstetric data were collected. Methodology: The severity of MSAF was classified into three categories: Grade I (thin), Grade II (moderate), and Grade III (thick). The incidence of puerperal pyrexia was monitored during the postpartum period. Statistical analysis was performed to assess the relationship between MSAF severity, mode of delivery, and the development of puerperal pyrexia. Results: Of 120 women, 23 (19.2%) developed puerperal pyrexia. The incidence was significantly higher in women with Grade III MSAF (38.2%) compared to those with Grade I (8.3%) and Grade II (14%). Cesarean delivery was also associated with a higher incidence of puerperal pyrexia (26.9%). Clinical Implication: Identifying MSAF severity and mode of delivery as risk factors can help healthcare providers in early detection and management of puerperal pyrexia. Conclusion: The study found a significant association between the severity of MSAF, mode of delivery, and puerperal pyrexia, suggesting the importance of close monitoring in at-risk patients. Keywords: Cesarean section, meconium-stained amniotic fluid, puerperal pyrexia, postpartum complications, vaginal delivery.